Neuromuscular Electrical Stimulation in Facial Aging: an Integrative Literature Review - Márcia Cristina Dias Consulin; Louise Idalgo Vasques; Gislaine Ricci Leonardi (Universidade de São Paulo, 2023)
ABSTRACT Despite of being a natural physiological process, aging is considered a degenerative process with evident effects on aging skin, such as reduced elasticity, wrinkles, reduced facial fat and muscle tone, sagging, changes in facial contour, and sarcopenia on the face. These changes can generate social stigma, suffering, and psychological discomfort for the patient. Thus, this study aimed to evaluate the effectiveness of Neuromuscular Electrical Stimulation (NMES), a technique used in physical therapy for muscle training, in attenuating the signs of facial aging. For this purpose, a scientific survey of publications indexed on the Medline (PubMed), CINAHL, Embase, PEDro, Lilacs, ERIC, Scopus, Web of Science, and Google Scholar databases was conducted and, based on pre-established criteria, two relevant publications for the topic were selected for discussion. The scientific literature regarding the use of NMES to attenuate the signs of aging is still very scarce. The survey showed the need to discuss the current state of knowledge. Our results suggest that, theoretically, NMES could be a promising method to attenuate the signs of aging; however, there are still no conclusive results regarding the clinical effectiveness of using NMES in the facial muscles since few studies relate NMES to facial rejuvenation. More studies are needed, with greater methodological rigor and low level of bias, using precise techniques in the evaluation and allowing to interpret with greater scientific commitment of the physiological mechanism of the muscular stimulus and its interrelation with the integumentary system, proving its effectiveness in the improvement of skin appearance.